2021
DOI: 10.31117/neuroscirn.v4i4.107
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of smartphone addiction in emerging adults evaluated using brain morphometry and resting-state functional MRI

Abstract: The characteristics of smartphone addiction (SPA) can be evaluated by neuroimaging studies. Information on the brain structural alterations, and effects on psychosocial wellbeing, however, have not been concurrently evaluated. The aim of this study was to identify abnormalities in gray matter volume using voxel-based morphometry (VBM) and neuronal functional alterations using resting-state functional MRI (rs-fMRI) in emerging adults with SPA.  We correlated the neuroimaging parameters with indices for psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this context, recent studies have shown that the specific brain structural variations that are identified may strongly depend on the choice of processing pipeline (see Zhou et al ., 2022 for a methodological evaluation of the effects of choice of processing pipeline on brain structural analyses). Moreover, some of the identified studies focused in their analysis on specific hypothesis-driven brain regions such as the brain stem (Cho et al ., 2021 ) or specifically on striatal morphology (Yoo et al ., 2021 ), whereas other studies used whole-brain analytic approaches (Horvath et al ., 2020 ; Rashid et al ., 2021 ). Further complicating matters is the use of different rigor in the brain analysis and in the level of description of the analyses used, such that for several studies the exact multiple comparisons approach used remains unclear.…”
Section: Smartphone (Over-)use and Brain Structure (Structural Mri St...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, recent studies have shown that the specific brain structural variations that are identified may strongly depend on the choice of processing pipeline (see Zhou et al ., 2022 for a methodological evaluation of the effects of choice of processing pipeline on brain structural analyses). Moreover, some of the identified studies focused in their analysis on specific hypothesis-driven brain regions such as the brain stem (Cho et al ., 2021 ) or specifically on striatal morphology (Yoo et al ., 2021 ), whereas other studies used whole-brain analytic approaches (Horvath et al ., 2020 ; Rashid et al ., 2021 ). Further complicating matters is the use of different rigor in the brain analysis and in the level of description of the analyses used, such that for several studies the exact multiple comparisons approach used remains unclear.…”
Section: Smartphone (Over-)use and Brain Structure (Structural Mri St...mentioning
confidence: 99%
“…Table 2 shows studies investigating the neural correlates of SmUD tendencies using fMRI. Most previous studies employed a resting state fMRI approach examining associations between SmUD tendencies and the intrinsic functional organization of the brain (Ahn et al ., 2021 ; Chun et al ., 2018 ; Horvath et al ., 2020 ; Kwon et al ., 2022 ; D. Liu et al ., 2022 ; Lou et al ., 2019 ; Paik et al ., 2019 ; Pyeon et al ., 2021 ; Rashid et al ., 2021 ; Schmitgen et al ., 2022 ; Zou et al ., 2022 ). A direct comparison between the studies is hindered by differences in the methodological approaches, ranging from different preprocessing methods to different network analytic strategies.…”
Section: Smartphone (Over-)use and Functional Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…The DMN is a constellation of nodes in the brain that are functionally connected to the posterior cingulate cortex node in the brain and appear to be activated when a person is at rest and not performing any tasks. Historically, the FC of the nodes of the DMN have been implicated with altered brain morphometry in various neurological and psychological disorders (Rashid et al, 2021). A previous study has revealed that decreased FC is widespread in the brain of AD subjects compared to HC subjects, particularly involving the nodes of the DMN (Soman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SBA is useful for the detailed analysis of a particular Region of Interest (ROI), to measure functional changes between participants and to reveal the FC among the nodes of the DMN (19, 33). Historically, DMN FC has been implicated with altered brain morphometry in various neurological and psychological disorders (34). Previous study has revealed that there is decreased FC that is widespread in the brain of AD compared to HC participants, particularly involving the nodes of the DMN (35).…”
Section: Introductionmentioning
confidence: 99%